Design and Analysis of Reinforced Fiber Composites - Marcal, Pedro V.; Yamagata, Nobuki (Springer International Publishing : Imprint: Springer, 2016)
The papers in this volume present a broad range of applications for reinforced fiber composites - from thin shell structures to tires. Linear and nonlinear structural behavior (from linear buckling to nonlinear yelding and fracture) are discussed as well as different materials are presented. Latest developments in computational methods for constructíons are presented which will help to save money and time. This is an edited collection of papers presented at a symposium at the WCCM, Barcelona, 2014.